2017
DOI: 10.1111/jpm.12389
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic role of mental health nurses in psychiatric intensive care: A mixed‐methods investigation in an inner‐city mental health service

Abstract: Introduction Despite indications that therapeutic interaction is beneficial for patients and for nurses' job satisfaction in acute psychiatric care, research shows a small amount of nurses' time is spent on such activity. Aims This study investigated the actual and potential therapeutic role of the mental health nurse in psychiatric intensive care, where admission is due to violence or aggression. Methods In a mixed-methods concurrent triangulation design, clinician and patient activity was observed using a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(65 citation statements)
references
References 38 publications
3
62
0
Order By: Relevance
“…The observational findings in this study, the enabling factors identified, point in the same direction and thereby add to these conclusions. McAllister and McCrae () state that therapeutic engagement cannot be enforced by rule. Our standpoint is that TT itself, with its emphasis on togetherness, both enables TT and brings out engagement in patients and staff – indeed a circular feedbacking process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observational findings in this study, the enabling factors identified, point in the same direction and thereby add to these conclusions. McAllister and McCrae () state that therapeutic engagement cannot be enforced by rule. Our standpoint is that TT itself, with its emphasis on togetherness, both enables TT and brings out engagement in patients and staff – indeed a circular feedbacking process.…”
Section: Discussionmentioning
confidence: 99%
“…This design was chosen based on the conviction that quality interactions, with their potential benefits for both patients and staff, were needed for the systems as a whole and not only for certain individuals. This conviction is confirmed by McAllister and McCrae () who describe units as ecosystems where interactions, relationships, and the organization directly influence patient and staff engagement. Any change in one of these components has the potential to positively or negatively influence the level of engagement within the system.…”
Section: Methodological Discussionmentioning
confidence: 99%
“…With the acute focus on symptom reduction and with a very unwell consumer, attention to nurse–consumer therapeutic engagement may not be the immediate priority, particularly if workloads are high (McAllister & McCrae ; Pazargadi et al . ; Snell, Crowe & Jordan ).…”
Section: Why Are Meaningful ‘Consumer Involved’ Care Plans Not Alwaysmentioning
confidence: 99%
“…With the acute focus on symptom reduction and with a very unwell consumer, attention to nurse-consumer therapeutic engagement may not be the immediate priority, particularly if workloads are high (McAllister & McCrae 2017;Pazargadi et al 2015;Snell, Crowe & Jordan 2009). With high workloads, professional mental health nursing practice has been described as crisis management that prevents nurses from fulfilling their own role expectations and from meeting the needs of the consumer (Hummelvoll & Seversinsson 2001;Cleary 2003Cleary , 2004Fourie et al 2005).…”
Section: Factors Hindering Nurse-consumer Therapeutic Engagementmentioning
confidence: 99%
“…The body of research evidence in relation to adult PICU is much better established (Gwinner & Ward 2013). However, several studies have concluded that there remains no evidence regarding the efficacy of treatment approaches in PICU environments and there is an absence of clearly articulated principles and practices of nursing care in these environments (Bowers 2012;Gwinner & Ward 2013;McAllister & McCrae 2017).…”
Section: State Of Research On Camhs Picumentioning
confidence: 99%